PENGARUH LATAR BELAKANG KELUARGA TERHADAP SUKSESI BISNIS DENGAN KOMUNIKASI KELUARGA SEBAGAI VARIABEL MEDIASI PADA MAHASISWA KEWIRAUSAHAAN UNIVERSITAS MUHAMMADIYAH GRESIK - Firdausi, Aisyah Laili Habibah; Respati, Putra Panji (POLITEKNIK LP3I JAKARTA, 2026)
Family businesses contribute significantly to the national economy, especially in the micro, small, and medium enterprise (MSME) sector. The sustainability of family businesses is largely determined by the succession process, namely the transfer of leadership from the founding generation to the next generation. This study was conducted to examine the influence of family background on succession in family businesses by considering family communication as a mediating variable among students majoring in Entrepreneurship at Universitas Muhammadiyah Gresik. The novelty of this study lies in the analysis of the role of family communication that mediates the relationship between family background and business succession in the context of the younger generation, especially students as potential successors to family businesses. This study was conducted using a quantitative method through a questionnaires. The research group consisted of students who came from business owning families, with a sample size of 66 respondents. Data collection was carried out through a questionnaire based on indicators of family background, family communication, and business succession, which was then analyzed using the Partial Least Squares (PLS) program. The results of the study prove that family background had a significantly influences family communication (T-statistic = 3,065) and business succession (T-statistic = 14,754). In addition, family communication also has a significant effect on business succession (T-statistic = 2,275), thus acting as an intermediary that strengthens the relationship between family background and readiness to face the succession process.